2022
DOI: 10.3390/ma15082742
|View full text |Cite
|
Sign up to set email alerts
|

Interpretable Machine Learning Algorithms to Predict the Axial Capacity of FRP-Reinforced Concrete Columns

Abstract: Fiber-reinforced polymer (FRP) rebars are increasingly being used as an alternative to steel rebars in reinforced concrete (RC) members due to their excellent corrosion resistance capability and enhanced mechanical properties. Extensive research works have been performed in the last two decades to develop predictive models, codes, and guidelines to estimate the axial load-carrying capacity of FRP-RC columns. This study utilizes the power of artificial intelligence and develops an alternative approach to predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
0
18
0
Order By: Relevance
“…Previous studies in the area of optimal structural dimensioning mostly attempted to minimize structural cost or weight for a single load case [ 8 , 9 ]. More recent studies in the area attempted to develop general-purpose predictive models based on a dataset of structural configurations with known structural behavior [ 21 , 22 ]. However, the availability of experimental or numerical data describing the structural behavior is a major limiting factor in the training of robust predictive models since the size of the database used in the training of these predictive models is a decisive factor that effects to what extent these models could be used reliably.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in the area of optimal structural dimensioning mostly attempted to minimize structural cost or weight for a single load case [ 8 , 9 ]. More recent studies in the area attempted to develop general-purpose predictive models based on a dataset of structural configurations with known structural behavior [ 21 , 22 ]. However, the availability of experimental or numerical data describing the structural behavior is a major limiting factor in the training of robust predictive models since the size of the database used in the training of these predictive models is a decisive factor that effects to what extent these models could be used reliably.…”
Section: Discussionmentioning
confidence: 99%
“…Bekdaş et al [ 21 ] demonstrated the high accuracy of different Ensemble Learning Algorithms in predicting the optimal wall thickness of reinforced concrete cylindrical walls. Cakiroglu et al [ 22 ] developed predictive models using Ensemble Learning Algorithms to estimate the axial load-carrying capacity of FRP-reinforced concrete columns.…”
Section: Introductionmentioning
confidence: 99%
“…[63][64][65][66][67][68][69][70]. Estimations of various characteristics of conventional and advanced concretes, such as durability, thermal characteristics, and mechanical characteristics, have been extensively covered in previous studies [71][72][73][74].…”
Section: Categories Of Machine Learningmentioning
confidence: 99%
“…The other objective of the current study is to develop opensource, Python-based ML models to estimate the axial load-carrying capacity of CFDST columns to further help researchers utilise the developed models to improve the framework once additional experimental data are available [ 32 ].…”
Section: Introductionmentioning
confidence: 99%